L’homme espagnol, la cultura popular y el diálogo entre pasado y presente - Tomás A. Mantecón Movellán (Les Cahiers de Framespa)
This article explains the historiographic moment in which L’homme espagnol was published analyzing the most important scientific contributions of that moment in the field of the history of popular culture. The elements that contributed to building the foundations of modern historiography on this matter are underlined here, as well as their validity in current research to overcome uncritical archetypes and prejudices.